Novel Approach to Proficiency Testing Highlights Key Practice Variations in Cancer Biomarker Delivery - Kassandra R. Bisson; Jennifer R. Won; Andrea Beharry; Michael D. Carter; Shaan Dudani; John G. Garratt; Jonathan M. Loree; Stephanie Snow; Stephen Yip; Brandon S. Sheffield (Journal of Molecular Pathology, 2024)
Biomarkers are fundamental to modern oncology practice, forming a close link to pathology practice. Pathology results must be accurate, timely, comprehensive, and comprehendible. External proficiency testing is a key tool in maintaining biomarker quality. Here, we demonstrate the feasibility and utility of a novel end-to-end proficiency testing exercise exploring accuracy, turnaround time, and communication. Challenge specimens were made using resected colon cancer tissue, each paired with a fictional clinical vignette, and distributed to participants who were asked to provide all molecular testing required and return a final report for each case upon completion. Reports were redistributed to an assessor team including medical oncologists, each of whom was asked to recommend a systemic therapy based on each lab’s biomarker report. Participants were graded based on their ability to guide oncologists to the correct treatment. Eight laboratories participated. Three laboratories were found to have suboptimal results, two leading oncologists to incorrect therapeutic prescriptions, and one withdrawn. Turnaround time ranged from 6 to 86 days (median 24). Substantial qualitative reporting differences were identified. This study demonstrates the feasibility of end-to-end proficiency testing. The approach provides considerable value beyond analytic accuracy, including specimen management, turnaround time, and communication of results. Results suggest that reporting differences may lead to treatment disparities. This style of quality assurance will help reinforce good practices critical to the delivery of precision cancer care.